Association between anti-thymocyte globulin exposure and CD4+ immune reconstitution in paediatric haemopoietic cell transplantation: a multicentre, retrospective pharmacodynamic cohort analysis. Issue 5 (May 2015) - Admiraal, Rick; van Kesteren, Charlotte; Jol-van der Zijde, Cornelia M; Lankester, Arjan C; Bierings, Marc B; Egberts, Toine C G; van Tol, Maarten J D; Knibbe, Catherijne A J; Bredius, Robbert G M; Boelens, Jaap J
Summary: Background: Anti-thymocyte globulin (ATG) was introduced into the conditioning regimen in haemopoietic cell transplantation (HCT) to prevent graft-versus-host-disease (GvHD) and graft failure. However, ATG can also cause delayed immune reconstitution of donor T cells. We studied the relation between exposure to active ATG and clinical outcomes in children. Methods: In this retrospective analysis, all patients (age 0·2–23 years) receiving their first HCT between April 1, 2004, and April 1, 2012, who received ATG (thymoglobulin) in two Dutch paediatric HCT programmes were included. The cumulative dose of ATG was chosen according to local protocols and was given intravenously over 4 days consecutively. ATG exposure measures (maximum concentration, concentration at time of HCT, clearance, days to reach a concentration below the lympholytic concentration of one arbitrary unit [AU] per mL, total area under the curve [AUC], AUC before HCT, and AUC after HCT) were calculated using a validated population pharmacokinetic model. The main outcome of interest was immune reconstitution (defined as CD4+ T cells >0·05 × 10 9 cells per L in two consecutive measurements within 100 days). Other outcomes of interest were survival, acute and chronic GvHD, and graft failure. We used Cox proportional hazard models, logistic regression models, and Fine-Gray competing risk regressions for analyses. Findings: 251 patients were included. The chance of successful immune reconstitution decreased as the ATG AUC after HCT increased (odds ratio 0·991, 95% CI 0·987–0·996; p<0·0001). Within the cord blood group, we noted decreased immune reconstitution above the lowest AUC quartile (≥20 AU × day/mL; p=0·0024), whereas in the bone marrow or peripheral blood stem cell group, decreased immune reconstitution was noted only in the highest quartile (≥100 AU × day/mL; p=0·0024). Successful immune reconstitution by day 100 was associated with increased overall survival (hazard ratio [HR] 0·49, 95% CI 0·29–0·81; p=0·0047) caused by reduced non-relapse mortality (0·40, 0·21–0·77; p=0·0062), and relapse-related mortality in myeloid leukaemia (0·25, 0·08–0·76; p=0·015). An AUC before transplantation of at least 40 AU × day/mL resulted in a lower incidence of acute GvHD (grade 2–4 HR 0·979, 95% CI 0·963–0·994; p=0·0081; and grade 3–4 0·975, 0·952–0·998; p=0·033), chronic GvHD (0·983, 0·968–0·998; p=0·029), and graft failure (0·981, 0·965–0·997; p=0·020) compared with an AUC of less than 40 AU × day/mL. Interpretation: These results stress the importance of improving the efficacy and safety of ATG in HCT by amending dosage and timing. Individualised dosing and timing of ATG to aim for optimum exposure before and after HCT could result in improved outcomes after paediatric HCT. Funding: Dutch Organization for Scientific Research.